Tribological behavior of N-doped ZnO thin films by metal organic chemical vapor deposition under lubricated contacts - Bolutife Olofinjana; Uchenna Sydney Mbamara; Oyelayo Ajayi; Cinta Lorenzo-Martin; Eusebius Ikechukwu Obiajuuwa; Ezekiel Oladele Bolarinwa Ajayi (Friction)
Abstract N-doped ZnO thin films were deposited on 304L stainless steel through the pyrolysis of zinc acetate and ammonium acetate in different ratios at a temperature of 420 °C using metal organic chemical vapor deposition. Compositional and structural analyzes of the films were performed by using Rutherford backscattering spectroscopy and X-ray diffraction. The frictional behavior of the thin films and 304L stainless steel substrate was evaluated using a ball-on-flat configuration with reciprocating sliding under marginally lubricated and fully flooded conditions. Al alloy (2017) was used as ball counterface, while basestock synthetic polyalfaolefin oil (PAO10) without additives was used as lubricant. The flat and ball counterface surfaces were examined to assess the wear dimension and failure mechanism. Under marginally lubricated condition, N-doped ZnO thin films provided significant reduction in friction, whereas the films have minimal or no effect in friction under fully flooded condition. N-doped ZnO thin films showed a significant effect in protecting the ball counterface as wear volume was reduced compared with that of the substrate under the marginally lubricated condition. Under the fully flooded condition, with the exception of one of the films, the wear volume of the N-doped ZnO thin films ball reduced compared with that of the substrate. In all the ball counterfaces for N-doped ZnO thin films under both conditions, wear occurred through abrasive mechanism of various degrees or mild polishing. Thus, superfluous lubrication of N-doped ZnO thin films is not necessary to reduce friction and wear.